Successful open defecation-free intervention in low- and middle-income countries: a qualitative synthesis systematic review protocol - Vera Yulyani; Iswanto Iswanto; Daniel Daniel; Fitrina Mahardani Kusumaningrum; Fatwa Sari Tetra Dewi (BMJ Open)
Introduction The results of open defecation-free (ODF) programmes vary greatly, especially in low- and middle-income countries (LMICs). This study will systematically investigate available qualitative research to identify the elements contributing to open defecation programmes’ effectiveness in various situations across LMICs. Furthermore, this review seeks to identify gaps in the available literature and areas that require additional investigation and action.Methods and analysis Inclusion criteria were developed considering issues related to open defecation in LMICs, sanitation interventions and behavioural change. Research examining sanitation interventions in schools, shelters, disability communities and virtual communities was excluded, as the review focused exclusively on community-based interventions. Studies published in English and Indonesian were included without limitation of the initial year until 31 January 2025. Systematic research will be carried out using ScienceDirect, PubMed, ProQuest and Scopus databases. Information from grey literature, including conference proceedings and reports from relevant organisations, will be systematically searched using Google Scholar and the websites of leading institutions, such as the WHO, UNICEF and WaterAid. This systematic review did not impose any restrictions on the place and date of publication. Two reviewers followed Joanna Briggs Institute guidelines in selecting studies, conducting critical appraisal using confidential tools and extracting data using a structured approach. Data synthesis will be performed using meta-aggregate methods to identify the themes. A ConQual Summary will be used to assess confidence in the findings.Ethics and dissemination The findings of the systematic review will be disseminated through a publication in a peer-reviewed journal and presented at a relevant conference. Since the data used will not contain individual patient information, ethical approval is unnecessary.PROSPERO registration number CRD42023408851.